Risk profiles for athlete burnout in adolescent elite athletes: A classification analysis. (March 2019) - Granz, Hanna L.; Schnell, Alexia; Mayer, Jochen; Thiel, Ansgar
Abstract: Objectives: All adolescent elite athletes are subjected to extensive additional stressors compared to their age-mates, but only some show symptoms of athlete burnout (ABO). In this study, we aim to decipher which features characterize adolescent elite athletes with especially high and low ABO symptomatology. Methods and design: We used data from the GOAL study ("German Young Olympic Athletes' Lifestyle and Health Management Study") in which 1138 young elite athletes ( M  = 16.33 years, SD  = 1.10) were assessed regarding ABO symptomatology (via the ABQ) and several correlate features. Cross-sectional data were analysed via Classification Tree Analysis in order to identify and characterize groups with extreme levels of ABO symptomatology. Results: Results indicate different relevant correlates for each of the three burnout symptoms. Comprehensive analyses revealed specific combinations of high and low-risk characteristics. High-risk characteristics included being involved in a technical, endurance, aesthetic or weight-dependent sport, training under an autocratic or laissez-faire coach, high subjective stress outside of sport, a low willingness to make psychological sacrifices, lack of sleep, and being female. Low-risk characteristics included fewer hours of training, low social pressure, low subjective stress outside of sport, a high willingness to make psychological sacrifices, and a high health satisfaction. Conclusion: Our results provide a necessary base for future hypothesis-testing studies in the field of adolescent ABO, as well as important insights for practitioners in the field, which can aid to create a base for optimal athletic performance. Highlights: Our results support (athlete) burnout as a function of context and personal factors. We identified burnout profiles of risk and protective characteristics. High stress outside of sport and social pressure characterize high risk groups. Fewer hours of training and a high health satisfaction characterize low risk groups.